Yahoo Web Search

  1. Ad
    related to: t
  1. For t in quadrant III, cos( t ) < 0. Using the Pythagorean identity in this case cos( t ) = - √(1 - sin²( t )). Note the negative sign. When it is defined, we know...

    1 Answers · Science & Mathematics · 27/11/2012

  2. 8( t /( t -2))^2 - 2( t /( t -2)) - 3 = 0 let x = t /( t - 2) 8 x^2 - 2x - 3 = 0 (4x - 3)(2x + 1) = 0 x = 3/4 or x = -1/2 so t /( t - 2) = 3/4 4t = 3( t -2) t = -6 or t /( t - 2) = - 1/2 2t = -( t - 2) 3t = 2 t = 2/3 Ans t = -6 or t = 2/3

    5 Answers · Science & Mathematics · 15/07/2008

  3. T -Mobile is a German provider, owned by Deutsche... began to brand its subsidiaries with the T - prefix. In 2002, as Deutsche Telekom consolidated...

    4 Answers · Consumer Electronics · 16/01/2011

  4. -sin( t ) + cos(2t) = 0 cos(2t) = sin( t ) Formula : cos(2t) = cos^2( t ) - sin^2( t ) = 1 -sin^2( t ) - sin^2( t ) = 1-2sin^2( t ...1 Now get back to the notation sin( t ) = -1 => t = 3pi/2 which is greater than pi/2 so this...

    1 Answers · Science & Mathematics · 30/06/2010

  5. v( t ) = ( t ^7)^(1/2) - t ^(1/2) v'( t ) = 1/2( t ^7)^(-1/2) * (7t^6) - (1/2) t ^(-1/2) v'( t ) = (7t^6)/2( t ^7)^(1/2) - 1/2( t ^1/2) and then take the second derivative of that - i won...

    2 Answers · Science & Mathematics · 14/10/2009

  6. ( t -(1/ t ))/2 Multiply -1 by 1/ t Denominators must be equal to add fractions...2 * ((( t -1)( t +1))/2t) Find the derivative. d/dt (( t -1)( t +1))/2t Use the quotient rule. The quotient rule ...

    2 Answers · Science & Mathematics · 19/10/2012

  7. x = t / (1 + t ); y = ln(1 + t ) dx/dt = ((1 + t )[1] - t [1]) / (1 + t )² dx/dt = 1 / (1 + t ...dt = √{(dx/dt)² + (dy/dt)²} ds/dt = √{(1 / (1 + t )²)² + (1 / (1 + t ))²} ds/dt = √{1 + (1...

    1 Answers · Science & Mathematics · 21/02/2010

  8. t /3-2=9 t /3=9+2 t /3=11 t =11*3 t =33 Answer: t =33 CHECKING: LEFT SIDE:33/3-2=11-2=9 RIGHT SIDE: 9 LEFT SIDE=RIGHT SIDE THEREFORE t =33

    2 Answers · Education & Reference · 30/04/2011

  9. sin( t ) = 4/5 cos( t ) = 3/5 a) sin(pi - t ) = sin(pi)cos( t ) - sin( t )cos(pi) => 0 * cos( t ) - sin( t ) * (-1... t ) = -3/5 (-3/5 , 4/5) b) sin(- t ) = -sin( t ) = -4/5 cos(- t ) = cos( t ) = 3/5 (3/5 , -4/5) c) sin( t - pi) = sin( t )cos(pi...

    1 Answers · Science & Mathematics · 04/11/2011

  10. ∫(2 t ) (e^ t ) dt integrate by parts u = 2t , dv = e^ t dt du = 2 dt, v = e^ t ∫u dv = uv - ∫v du => ∫(2t) (e^ t ) dt = (2t) (e^ t ) - ∫(2) (e^ t ) dt = (2t) e^ t - 2e^ t + C = 2e^ t ( t - 1) + C

    2 Answers · Science & Mathematics · 02/02/2010

  1. Ad
    related to: t
  1. Try asking your question on Yahoo Answers